PENGARUH STRES KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS LINGKUNGAN HIDUP DAN KEHUTANAN DI KABUPATEN SUMEDANG - Rika Kusdinar; Ikhsan Zakky; Nuranisa; Sekar Asih Kumala Dewi; Yusup Sanjaya; Willy Tanu Wijaya (JRPA - Journal of Regional Public Administration, 2020)
The purpose of this study was to determine work stress, to determine employee productivity, to know the relationship between work stress and employee productivity and to determine the effect of work stress on employee productivity in the Department of Environment and Forestry, Sumedang Regency. Stress is an inability regarding the threats faced by a human being mentally, physically, emotionally, and spiritually which at one time can affect the physical health of the human being. Stress is our perception of a situation or condition in our own environment. Another definition states that stress is a condition of tension that affects one's emotions, thinking processes, and conditions. Meanwhile, productivity is a measure of the use of resources in an organization which is usually expressed as a ratio of the output achieved with the resources used (input). The method used in this research is quantitative research methods that examine specific populations, data collection using instruments, statistical analysis, with the aim of testing predetermined hypotheses. Meanwhile, data collection was carried out by means of library research and field studies in the form of observation and questionnaires to 63 respondents in the Environment and Forestry Service of Sumedang Regency.The results of this study, obtained a description of job stress including good criteria with a percentage of 81.47%, employee productivity including good criteria with a percentage of 82.63%. Then the job stress variable (X) affects the employee productivity variable (Y) by 24.9%. While the rest (100% - 24.9% = 75.1%) is influenced by outside variables that are not studied.There are several suggestions, one of which is that the Sumedang District Environment and Forestry Service has a meeting forum as a means to discuss or evaluate employee work results so that employee productivity at the Environment and Forestry Service in Sumedang Regency is better.